Protected natural areas: analysis of the progress of legal coverage for environmental protection: 1990-2024 - Vasquez Sanchez, Jose Ronald (2024)
Natural protected areas (NPAs) are spaces designated for the conservation of biodiversity and the maintenance of essential ecological processes. These areas, which include national parks, biological reserves and habitat management areas, play a crucial role in protecting flora, fauna and ecosystems from anthropogenic threats and provide various ecosystem services. However, despite these benefits, their implementation in Peru has not taken on great relevance. This article analyzes the evolution of legal coverage for environmental protection in the period 1990-2024, and highlights the advances and challenges in the implementation of conservation policies. The research corresponds to the descriptive type, with a documentary research approach. The results obtained subject the decades of 1990, 2000, 2010 and 2020 to a comparative analysis, in addition to analyzing the judgment of the state of sustainability related to Peru’s NPAs around international standards.